2021
DOI: 10.1007/s12013-021-00988-9
|View full text |Cite
|
Sign up to set email alerts
|

Current Knowledge on the Biology of Lysophosphatidylserine as an Emerging Bioactive Lipid

Abstract: Lysophosphatidylserine (LysoPS) is an emerging lysophospholipid (LPL) mediator, which acts through G protein-coupled receptors, like lysophosphatidic acid (LPA) and sphingosine 1-phosphate (S1P). LysoPS is detected in various tissues and cells and thought to be produced mainly by the deacylation of phosphatidylserine. LysoPS has been known to stimulate degranulation of mast cells. Recently, four LysoPS-specific G protein-coupled receptors (GPCRs) were identified. These GPCRs belong to the P2Y family which cove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 88 publications
(130 reference statements)
0
37
0
Order By: Relevance
“…LysoPS activates these receptors at a few micromolar concentrations that are not cytotoxic [ 38 , 48 , 49 ]. Moreover, the functional effects of LysoPS are often blocked by inhibitors of specific G proteins coupled with each GPCR [ 50 ]. In our hands, NCI-H292 cells do not express any of the four GPCRs, as determined by FACS and western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LysoPS activates these receptors at a few micromolar concentrations that are not cytotoxic [ 38 , 48 , 49 ]. Moreover, the functional effects of LysoPS are often blocked by inhibitors of specific G proteins coupled with each GPCR [ 50 ]. In our hands, NCI-H292 cells do not express any of the four GPCRs, as determined by FACS and western blot analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is little information about the level and pathological role of LysoPS in inflamed lungs. Several enzymes that specifically synthesize and degrade LysoPS have recently been identified [ 50 , 51 , 57 ]. PS-PLA1 is a crucial enzyme that synthesizes LysoPS extracellularly [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lysophosphatidylserine (Lyso-PS) has earned an increasing interest in the literature in recent years [ 14 ]. It has become clear that Lyso-PS is present in the CNS and in the immune system and its receptors have been characterized [ 15 ]. Further studies have shown that Lyso-PS is showing immunomodulatory functions, and several studies have proven an important link between Lyso-PS and neurodegenerative as well as autoimmune diseases [ 15 ].…”
Section: Ngf and Lipid Moleculesmentioning
confidence: 99%
“…Given the important role of NGF and the other neurotrophins in both the CNS and the immune system, it is plausible to hypothesize that a direct interaction between Lyso-PS and NGF might be of important functional significance. It has been shown that Lyso-PS is involved in histamine degranulation in mast cells [ 15 ]. Different sets of experiments have proven that there is a powerful synergism between Lyso-PS and NGF in mast cells, activating histamine secretion at low Lyso-PS concentrations [ 16 , 17 ] and in the presence of extracellular Ca 2+ [ 18 ] and phospholipase D [ 19 ].…”
Section: Ngf and Lipid Moleculesmentioning
confidence: 99%
See 1 more Smart Citation